Do preventive interventions for children of mentally ill parents work? Results of a systematic review and meta-analysis - Thanhäuser, Martina; Lemmer, Gunnar; de Girolamo, Giovanni; Christiansen, Hanna (Current opinion in psychiatry, 2017)
The transgenerational transmission of mental disorders is one of the most significant causes of psychiatric morbidity. Several risk factors for children of parents with mental illness (COPMI) have been identified in numerous studies and meta-analyses. Many interventions have been developed for this high-risk group, but data about their efficacy are heterogeneous. The current meta-analysis reports on 96 articles including 50 independent samples from randomized controlled trials quantifying effects of preventive interventions for COPMI. Random effect models resulted in small, though significant Effect Sizes (ES) for programs enhancing the mother-infant interaction (ES = 0.26) as well as mothers' (ES = 0.33) and children's (ES = 0.31) behavior that proved to be stable over the 12-month follow-up, except for infants' behavior. Interventions for children/adolescents resulted in significant small effects for global psychopathology (ES = 0.13), as well as internalizing symptoms (ES = 0.17), and increased significantly over time, with externalizing symptoms reaching significance in the follow-up assessments as well (ES = 0.17). Interventions addressing parents and children jointly produced overall larger effects. Higher study quality was associated with smaller effects. There is a dearth of high quality studies that effectively reduce the high risk of COPMI for the development of mental disorders.